2006
DOI: 10.1016/j.ejvs.2005.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Containing Bioactive Peptides Promote Endothelialisation by Circulating Progenitor Cells: An In vitro Evaluation

Abstract: We report a new nanocomposite based biomaterial that has been demonstrated, in vitro, to promote endothelialisation from PBMCs containing EPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…19 It was also observed that POSS-PCU and uncoated culture dishes produced significantly fewer colonies than POSS-PCU-RGD. These results help us to conclude that ECs are capable of morphogenesis and have the ability to proliferate well.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…19 It was also observed that POSS-PCU and uncoated culture dishes produced significantly fewer colonies than POSS-PCU-RGD. These results help us to conclude that ECs are capable of morphogenesis and have the ability to proliferate well.…”
mentioning
confidence: 79%
“…When the endothelialization is implemented on the luminal surface of bypass grafts, it improves the lifetime and clinical results of the grafts. 19 The clinical studies done by researchers depict the benefits of lining PTFE vascular grafts with endothelial …”
Section: Nanocomposites To Improve Endothelialization Of Graftmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the improvement of the endothelialization of the luminal surface of bypass grafts, potentially improve their patency rate and overall clinical outcomes. 48 Studies have shown the clinical benefit of lining polytetrafluoroethylene (PTFE) vascular grafts with endothelial cells, particularly in lower limb arterial bypass grafts, 49 unlike native, uncoated polyethylene terephthalate grafts. In an in-vitro study using human umbilical vein endothelial cells (HUVECs), we assessed whether this nanocomposite is safe and compatible with in vitro cell cultures.…”
Section: Endothelialization Propertymentioning
confidence: 99%